Pengaruh Serbuk Batu Kapur Sampang Madura sebagai Subtitusi Semen terhadap Slump Beton - Santoso, Dwi Prima; Sutriono, Bantot; Rochmah, Nurul (CV. Information Technology Training Center - Indonesia (ITTC), 2025)
Madura, particularly the Sampang region, possesses significant reserves of carbonate minerals, notably limestone. The utilization of this local material as a construction element holds substantial potential, but requires investigation into how the substitution and addition of pulverized limestone affect the critical properties of concrete. This study focuses on the problem of how a combined 50% substitution of coarse aggregate with Sampang limestone and the incremental addition of pulverized limestone as an additive influences the workability of fresh concrete. The primary objective of this research is to evaluate and determine the effect of incremental percentages of Sampang pulverized limestone additive (0%, 5%, 10%, 15%, and 20%) on concrete workability, quantified by the slump test, for a concrete mix that already utilizes a 50% coarse aggregate substitution with limestone, aiming to identify the optimal composition. The methodology employed in this study is laboratory-based experimentation. The analytical technique applied is descriptive statistical analysis to compare the average slump values resulting from the variations in additive composition. The baseline concrete mix comprised a 50% substitution of coarse aggregate with limestone. Subsequently, the pulverized limestone powder was added at the predetermined additive percentages. The results indicate that the baseline mix (50% limestone substitution with 0% additive) yielded an average slump of 16.7 cm. The highest average slump value of 17.3 cm was recorded when the 50% substitution mix was further enhanced by a 5% additive composition. Conversely, increasing the additive proportion beyond 5% consistently reduced the slump, achieving the lowest workability of 15.0 cm at the 20% additive level. These findings suggest that the inclusion of 50